JURNALISME REPORTASE: SEBUAH PRODUK KOMERSIALISASI DALAM INDUSTRI TELEVISI - Aprinta, Gita (Jurnal The Messenger, 2012)
The freedom of press has given space to the growth of television industries in Indonesia. As we all know, since 2010 there are at least nine private television that established. This case has been impact to the public information fulfilness. Unfortunately as part of the capitalism industry, television should able to provide information that give two function, these is entertainment and journalism. Therefore, information is so often considered as commodity relate with the market mechanism that create television commercialization.This article aim to observe the bias of information that affected by journalism technique in the investigation program called. Reportase Investigasi through the approach Marxis capitalism where in the world of capitalism production is always relate with power and capital ownership.